Analisis Loyalitas Dan Perilaku Memiliki Organisasi Karyawan - Yurini, Rina, Dr.Moordiningsih,M.Si (2013)
Loyalty and organizational citizenship behavior of employees is an important factor to improve organization performance. The loyalty makes the employees to work to their maximum ability and provide maximum throughput. Through organizational citizenship behavior, employees will give more devotion and dedication than their simple job description. The research looked at the behavior of PT Aksara Solopos employes. SOLOPOS, newspaper is published, was able to defeat the myth about city of Solo as a "Cemetery Newspaper". Without employees loyalty and organizational citizenship behavior, it was impossible for PT Aksara Solopos to evolve into big company and could become a holding company with several subsidiaries. The research was conducted using qualitative descriptive through the deployment of open ended questionnaire to 50 employees . The research was further strengthened by the observation and interviews of the management and distribution of questionnaires by email to the employees who have left the company. This study illustrated that the employees of PT Aksara Solopos have loyalty and organizational citizenship behavior. Although the employee turnover rate in the company ranged from 11 % - 17 % , but majority of employees ,or 80 % of them, claimed enjoy working in the company . On organizational citizenship behavior case, employees also claimed to have worked beyond job responsibilities and job descriptions . The main factors that influenced the employees behavior was comfortable, non-pressurized, working atmosphere and well-being support provided in PT Aksara Solopos.. Conclusion : PT Aksara Solopos employees loyalty and organizationalcitizenship behavior was influenced by working conditions and welfare services provided.